The impact of transformational leadership on the workplace well-being of employees with disabilities: series mediation and moderation process - Abdulaziz Alfalih; Wided Ragmoun (Frontiers in Public Health)
This paper investigates the impact of transformational leadership on workplace well-being for employees with disabilities through the integration of assistive technology (AT) and its influencing factors. Despite the growing recognition of the importance of inclusivity in the workplace, employees with disabilities frequently encounter barriers that can hinder their well-being and participation. This research examines how transformational leadership can shape the organizational context through the adoption, utilization, and effectiveness of AT in promoting employee well-being while also considering the impact of psychological factors. A questionnaire was employed to collect responses from 432 employees with disabilities. Based on the gathered data, Structural Equation Modeling (SEM) with SmartPLS was utilized to test the research hypotheses and produce results. The findings reveal that transformational leadership fosters a positive organizational context by nurturing a culture of inclusion and support with β = 0.081. This context promotes integrating assistive technology to enhance the well-being of disabled employees in the workplace. Additionally, the results confirm that transformational leadership encourages the development of psychological factors such as self-confidence and self-efficacy as key determinants of well-being, with β = 0.435. This paper contributes to the existing literature by providing a nuanced understanding of the relationship between transformational leadership, assistive technology, and the well-being of employees with disabilities. It offers comprehensive practical insights for organizations seeking to improve their inclusive practices and support employees with disabilities in achieving their full work potential.